Pembangkangan Doktrin dan Ajaran Muhammadiyah: Studi Terhadap Perilaku Keagamaan Warga Muhammadiyah di Kampung Muhammadiyah Warungboto Umbul Harjo Yogyakarta - Khoirul Anam (AN NUR: Jurnal Studi Islam, 2015)
There is an interesting phenomenon that occurred in the village of “Muhammadiyah” Warungboto Umbulharjo Yogyakarta, where residents of Muhammadiyah in this village runs a variety of unusual religious rituals performed by other Muhammadiyah members. The village is still run a wide variety of religious rituals that notabenenya conflicting doctrines and teachings of Muhammadiyah as a socio-religious organization that carries tajdid and puritan movement, such as dziba’an, litany, tahlilan, istighotsah, tingkeban, selametan, rebananan, yasinan and so forth. Moreover, the Muslim community Muhammadiyah in Warungboto also still very thick with syncretic religious rituals such as funerals, ceremonies of birth and marriage ceremonies. Clearly, these phenomena interesting to study because Muhammadiyah is known as an anti-religious social organizations against a wide variety of religious rituals are no rules in the Koran and Hadith. Muhamamdiyah even strongly condemned the various activities that smelled heresy, and superstition takhayyul as above. Considering there ketidaksingkronan between who should and that happened, the researchers feel challenged to seek answers to the phenomenon. This paper will examine about insubordination residents in Kampung Muhammadiyah Muhammadiyah Warungboto to the doctrine and teachings of Muhammadiyah.